Utilization of Fish Flour in Canned Concentrated Seasoning Stock for Thai Foods Preparation - Plernchai Tangkanakul; Payom Auttaviboonkul; Patcharee Tungtrakul; Mantana Ruamrux; Chidchom Hiraga; Kanjanarat Thaveesook; Montatip Yunchalad (Agriculture and Natural Resources, 2005)
Herring fish flour possessed high contents of protein, calcium and phosphorus at 64.70 g/100 g, 2,576 mg/100 g and 1,531 mg/100 g, respectively. Herring fish flour was used to replace fresh or dehydrated fish meat in developing five canned concentrated seasoning stocks for Thai food; Nam Ya Pla (fish curry sauce), Kaeng Som (spicy sour mixed vegetable), Kaeng Tai Pla (southern hot curry), Kaeng Kua Fag (red curry with wax gourd), and Kaeng Tae Po (red curry with swamp morning glory). Sensory test exhibited that a suitable amount of herring fish flour incorporated was 15% or 18% of curry paste, that accounted for 2.6-5.1% in the recipe. It was determined that 100 g canned stocks provided protein, calcium and phosphorus as 4.32 – 6.00 g, 126.5 – 136.4 mg and 83.9 – 108.6 mg, respectively. Calcium content of fish flour incorporated dishes was high, supplying 10-25% of the adult Recommended Daily Dietary Allowance in a 100 g portion.